Spinal manipulation and mobilization forces delivered treating sciatica: a case report - Siciliano, Theodore B.; Gudavalli, Maruti R.; Kruse, Ralph (Frontiers in Integrative Neuroscience, 2024)
Measuring the forces applied during spinal manipulation and its biomechanical effects on the spine are critically important in today’s research. This single case report discusses the potential benefit of accurately monitoring manipulative forces in treating low back pain with sciatica. The type of Force-Based spinal manipulation used to manage this case was Cox Technic Flexion Distraction Decompression spinal manipulation (CTFDD) care along with other ancillary modalities (pre-modulated electrical muscle stimulation (EMS), infra-red-light therapy (ILT), and a home stretching and strengthening program were part of this treatment plan). Patient presented with complaints of left lumbar spine pain which radiated into the left buttock, down the left leg and demonstrated an inability to dorsi-flex the left foot. Patient was concerned with this condition as the left leg pain and left lower extremity motor deficit was having a profound effect on the patient’s ability to perform activities of daily living and work. The patient was recommended to undergo spinal decompression surgery, which the patient did not want and elected to exhaust all alternative, non-surgical treatments first. A diagnosis of sciatica with a sequestered disc fragment and left lower extremity motor deficit was rendered through objective physical examination results and a review of a lumbar MRI study. Past interventions included prescription medications, physical rehabilitation, chiropractic, pain management, and a neurosurgical consultation. All past interventions prior to initiating CTFDD care provided minimal subjective and/or objective clinical improvement. This patient had a positive clinical outcome from a Force-Based CTFDD treatment plan along with other modalities consisting of pre-modulated electrical muscle stimulation (EMS), infra-red-light therapy (ILT), and a home stretching and strengthening program were part of this treatment plan. Force-Based Cox Technic Flexion Distraction Decompression spinal manipulation along with other modalities consisting of pre-modulated electrical muscle stimulation (EMS), infra-red-light therapy (ILT), and a home stretching and strengthening program has been found to be an alternative, non-surgical treatment for discogenic sciatica. Continued research is needed on Force-Based CTFDD spinal manipulation to further evaluate the neurological and biomechanical effects of the forces and motion applied to the spine to determine health benefits for the treatment of low back pain.